Diagnostic Methods in Primary Ciliary Dyskinesia. (March 2016) - Lucas, Jane S.; Paff, Tamara; Goggin, Patricia; Haarman, Eric
Summary: Diagnosing primary ciliary dyskinesia is difficult. With no reference standard, a combination of tests is needed; most tests require expensive equipment and specialist scientists. We review the advances in diagnostic testing over the past hundred years, with emphasis on recent advances. We particularly focus on use of high-speed video analysis, transmission electron microscopy, nasal nitric oxide and genetic testing. We discuss the international efforts that are in place to advance the evidence base for diagnostic tests.